Development Of Electronically Controlled Common Rail Fuel Injection System And Optimization Of Injector Parameters In Single Cylinder Diesel Engine - Peh, Ching Guan (Universiti Sains Malaysia, 2018)
Recent year, global energy demand grew rapidly due to growth in population, technology development and industrialization. The transportation sector is the major consumer of oil and produces a lot of air pollutants. Compression ignition diesel engine is gaining popularity over the year. However, it emits high nitrogen oxide (NOx) and particulate matter (PM) that cause health hazards. Precise control of fuel injection parameters can improve the diesel engine performance and reduce harmful emissions. This project aims to convert a single cylinder engine with pump-line-nozzle injection system to common rail injection system and optimize the injector parameters. At first, fuel delivery system has been installed and Engine controller unit (ECU) has developed. The ECU is based on Arduino microcontrollers, Arduino Mega and Arduino Uno were used in the development. Optimization of injector parameter is carried out by design of experiment software, and evaluation of optimum condition is performed. The percentage of error for optimization is less than 5%. Experiments have been carried out to evaluate the developed common rail fuel injection system. The results indicated that the developed ECU is capable to control injection timing, injection pressure and number of injections per cycle.